Hubungan Inisiasi Menyusu Dini (IMD) Dengan Involusi Uteri Ibu Post Partum Di RS Tni-Al Dr F X Suhardjo Tahun 2020 - Epi Dusra (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2021)
Involution is the process by which the uterus returns to its pre-pregnancy state. Abnormal involution or sub-involution is where the uterus fails to involute at the expected rate. The purpose of this study was to determine the relationship between Early Breastfeeding Initiation (Imd) and Uteri Involution of Post Partum Mothers at the TNI-AL Dr F X Suhardjo Hospital in 2020. The type of research used was an analytical survey research type with a Cross Sectional/Cross-Cutting approach. The population in this study were post partum mothers totaling 50 people. The sampling technique in this study was Proposive Random Sampling with a total sample of 44 people. Data analysis consisted of univariate and bivariate analysis using computerized analysis and presented in the form of tables and narratives. The results showed that the results of statistical tests showed that there was no significant relationship between IMD (Early Breastfeeding Initiation) and the incidence of uterine involution in postpartum mothers where p> 0.05 or p = 1.000. It was concluded that there was no significant relationship between early initiation of breastfeeding (IMD) of mothers after delivery and the incidence of post partum uterine involution.